2018
DOI: 10.1108/srj-05-2016-0086
|View full text |Cite
|
Sign up to set email alerts
|

How spirituality, climate and compensation affect job performance

Abstract: Purpose This paper aims to study the impact of four dimensions of workplace spirituality (engaging work, spiritual connection, mystical experiences and sense of community), corresponding with workplace climate and compensation on employee perceived job performance. Design/methodology/approach A sample of 207 individuals from an international hospital were interviewed. Preliminary research, sale assessment, correlations and regressions were carried out. Findings The findings suggest that there are strong, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 28 publications
7
20
2
7
Order By: Relevance
“…There is no broadly accepted meaning of the concept of spirituality (Markow & Klenke, 2005). Thanh Do (2018) agrees and says that the term spirituality is complex and miscellaneous. Ashforth and Pratt (2003) identify the primary components of workplace spirituality: purpose and meaning in life; a feeling of belonging and being interconnected, and individual fulfilments and satisfaction (Ashmos & Duchon, 2000;Sheep, 2006;DeKlerk, 2006).…”
Section: Workplace Spiritualitymentioning
confidence: 99%
See 2 more Smart Citations
“…There is no broadly accepted meaning of the concept of spirituality (Markow & Klenke, 2005). Thanh Do (2018) agrees and says that the term spirituality is complex and miscellaneous. Ashforth and Pratt (2003) identify the primary components of workplace spirituality: purpose and meaning in life; a feeling of belonging and being interconnected, and individual fulfilments and satisfaction (Ashmos & Duchon, 2000;Sheep, 2006;DeKlerk, 2006).…”
Section: Workplace Spiritualitymentioning
confidence: 99%
“…The dimension is characterised by having a common purpose and having a sense of being connected to others (Kinjerski & Skrypneck, 2006a). A number of scholars have been noted to embrace the idea of the link between job performance and the sense of collegiality (Thanh Do, 2018). For instance, Milliman et al (1999) argue that greater commitment and job performance are results of robust, purposeful targets and sense of community.…”
Section: Workplace Spiritualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lau (2015) verificou que medidas não financeiras usadas para medir e avaliar o desempenho do gestor são benéficas quanto a percepções de imparcialidade de procedimentos e clareza de papéis, e que seus efeitos na performance gerencial são indiretos, via clareza de papéis. Já Dahling, O'Malley e Chau (2015), Nae, Moon e Choi (2015) e Thornock (2016) concentraram-se nos efeitos do feedback sobre o desempenho individual, enquanto Tung (2018), Wang, Lu e Sun (2018) abordaram elementos dos sistemas de recompensas. Observaram que os incentivos intrínsecos e extrínsecos afetam positivamente a performance gerencial, mas os incentivos intrínsecos foram melhores preditores para promover o comportamento e o desempenho gerencial em comparação aos incentivos extrínsecos.…”
Section: Introductionunclassified
“…Results indicated that selective optimization with compensation helps in maintaining quality of performance so that nurses can forget the work load (Baethge, Müller & Rigotti, 2015). Data was also collected from 207 individuals from an international hospital and there was a significant and strong positive correlation between compensation and job performance (Do, 2018). LMX relationships are also partially based on the culture (Furunes, Mykletun, Einarsen, & Glasø, 2015).…”
Section: Compensation and Benefitsmentioning
confidence: 99%